Composition and Diversity of Soil Arthropods of Rajegwesi Meru Betiri National Park - Zayadi, Hasan; Hakim, Luchman; Leksono, Amin Setyo (Journal of Tropical Life Science, 2013)
Meru Betiri National Park (MBNP) is one of the nature conservation area thathas the potential of flora, fauna, and ecosystems that could develop as a nature-based tourism attraction. The existence of certain indicator species was related to estimation of stress level and disturbance on ecosystem stability for making strategic decisions about the restoration in this area. One of the important indicator species at forest ecosystem were soil arthropods. Aim this research were analyzed composition and diversity of soil arthropods at Rajegwesi, MBNP areas. The methods in this research used pitfall trap, measurement of distribution structure and soil arthropods composition based on the Shannon - Wiener index, Morisita similarity index and Importance Value Index (IVI). The number of families and individuals of soil arthropods found in the coastal area of Rajegwesi consists of 10 order with 21 families (702 individual). The number of individuals of the order Hymenoptera, Coleoptera, Collembola and Araneida was more widely found. Soil arthropods diversity index on each land use indicated that soil arthropod diversity in these areas were moderate. Soil arthropod community of orchards and forest had a similarity of species composition, whereas soil arthropod community of savanna had a similarity of species composition with paddy fields.